THE ROLE OF TRAVEL IN HUMAN LIFE - Sulaymonov, Tleugali; Fayzullayev, Sherzod (Science technology&Digital finance, 2023)
This article explores the socio-educational features of travel in maintaining and improving health and reflects on the conditions and opportunities of travel destinations in the nature of Uzbekistan, their role and importance in ensuring human health, their advantages.